Integration of Principles of Education for Sustainable Development in Mathematics Learning to Improve Student's Mathematical Problem Solving Ability - Putra, Jaya Dwi; Suryadi, Didi; Juandi, Dadang (IndoMath: Indonesia Mathematics Education, 2022)
This study aims to examine the differences in the improvement of mathematical problem solving ability between students who receive the jigsaw cooperative learning type based on education for sustainable development and students who receive conventional learning. This study is a quasi-experimental study with a non-equivalent control group design. The population in this study were students of grade 2 at one of the state high schools. The sample consisted of two classes which were selected by random sampling. The instrument used is a mathematical problem solving ability test. Based on the data analysis, it is concluded that the improvement students mathematical problem solving ability who received the jigsaw type of cooperative learning based on education for sustainable development was better than students who received conventional learning.